Judges’ Consideration In Deciding The Case Of The Rejection Of A Deceased Covid-19 Victim’s Funeral In Semarang - Setiawati, Sri; Siswanto, Bambang; Sumantri Riyanto, Ontran (International Journal of Educational Research & Social Sciences, 2022)
The handling of the dead bodies caused by the epidemic is one of the methods used to control disease outbreaks. The handling of the dead bodies itself has always been regulated in Article 16 of Government Regulation Number 40 of 1991 about Disease Outbreak Management, way before the COVID-19 pandemic happened. The purpose of this paper is to contribute to the advancement of legal science by expanding knowledge and providing references, particularly in the case of the rejection of COVID-19 victims' bodies, which is the subject of Ungaran District Court Ruling number 76/Pid.Sus/2020/PN Unr. This research is focused on these two problems: the legal review of the funeral law and the rejection of a deceased COVID-19 victim's funeral; and the judges’ consideration in deciding the case of the rejection of a deceased COVID-19 victim's funeral. Objectively, this research aims to describe the legal review of funerals and the rejection of a deceased COVID-19 victim's funeral, as well as the judges' considerations in deciding the case of the rejection of a deceased COVID-19 victim's funeral. The research was conducted using a normative juridical method with a statutory and conceptual approach. Primary and secondary legal materials are discussed and researched using an interpretation method with the aim of providing clarity on the existing legal materials related to the problems encountered. As such, the research results were as follows: Firstly, there are adequate laws and regulations for funeral management, including protocols for the burial of bodies due to infectious disease outbreaks. Refusing to bury a deceased COVID-19 victim is a penal act, both according to Law No. 4 of 1984 concerning Outbreaks of Infectious Diseases and the Criminal Code, and is an unlawful act according to Article 1365 of the Civil Code. Second, it was found that the judges decided the case by considering the law, the action, the mental attitude or guilt, and the penality. It is expected that there will be effective public education about the human rights inherent in a person even after death, as well as education about the dangers of stigmatizing COVID-19 patients and victims in efforts to combat the pandemic.